Adaptación y producción de gramíneas y leguminosas forrajeras en un ultisol de San Martin Perú - Rojas Reátegui, César Augusto (2002)
This research work was conducted in the fundo Miraflores, production and research at the Faculty of agricultural sciences of the National University of Sn Martin, located in the sector of Ahuashiyacu, Banda de Shilcayo district, province and Department of San Martín whereas with a forest ecosystem always seasonal green, in order to adapt and produce forage grasses and legumes in soil Ultisols of San Martin. The characteristics of the soil are: acid PH, low natural fertility and high concentration of aluminum. The experiment was carried out in a design of blocks totally at random, with arrangement of split plots; (with 12 treatments consisting of forage species (5) grasses and legumes (7) located in the plots and 4 ages, cutting (3, 6, 9 and 12 weeks) in the sub - plots). The phase setting, in a period of 4 months, indicates a good establishment in grass 5; heights of 60 to 80 cm between plants, population of 4 plants per m ^ 2 l 00 80% coverage. And legumes 7, there was also a good establishment, with the exception of Cratyua orgentea 18516 CiAT and the three ecotypes of Arachis pintoi CIAT 207; 208 and 30099, requiring more time to settle and fully take root. The evaluation of the production of dry matter during the season of maximum precipitation, tells us as the most noteworthy grass to Paspalum conjugatum ecotypes CIAT 26986 and CIAT 26989, with yields of 1.41; 4.11; 6,78 and 8.6 Tn / has MS and 1.45; 3.7; 5.08 and 9.83 Tn / has MS, respectively; in the ages of 3, 6, 9 and 12 weeks cut. The Brachiaria grasses 3 brir; antha cv marandu, B. decumbens CIAT 606 and JJ. dictyoneura CIAT 6133, had yields slightly lower than the two ecotypes of p. conjugatum; with foulbrood is checked and confirmed the good development and production of these 3 Brachiariilf under these conditions. The dry matter production of legumes 6 during the season of maximum precipitation was in the following way: at 3 weeks of age of cutting, it was highest in Arachis pintoi with its three ecotypes CIAT 30099, CIAT 207 and 208 CIAT with 764, 519 and 515 kgslha MS, respectively. At 6 weeks of age of Court have distinguished themselves as the best: a. pintoi with its three ecotypes CIAT 30099, ClAT 208 and 207 CIAT, together with C. macrocarpum CIAT 5065, with yields of 1. 66, l. 69, l.26 and 1.49 Tn / has MS, respectively. Pulses of higher yields at 9 weeks of age, were: Cratylia argentea CIAT 18516, A.pintoiCIAT 30099y Centrosema 5065, with macrocarpumCJAT: 5.61, 5.37 and 4.22 Tnlha MS, respectively, with no significant differences. The production of dry matter, during the time of minimum rainfall, was generally below the forage yield obtained at the time of maximum precipitation. In the grasses that have distinguished themselves as the higher-yielding, were: Brachiaria dictyioneu.ra CIAT 6133, with 0.61, 1.91, 2.69 and 5.3 Tn / has MS, at the age of 3, 6, 9 and 12 weeks cut. Pulses of higher dry matter yield, were: CIAT 18516 herring Cratylia, with yields of 1.25, 0.53, 2.19 and 4.69 Tn/ba Ms; following in order of importance the species: Desmodium ovalifolium CIAT 350 (0.33, 0.32, 1.38, and 2.32 Tn/ba MS) and Centrosema macrocarpum CIAT 5065, with yields of 0.19, 0.87, 1.25 and 2.21 Tn / has MS, to the ages of regrowth of 3, 6, 9 and 12 weeks. 3 ecotypes of a. pintoi had DM yields well below its performance obtained in the time of maximum precipitation. Also, in this period, this legume, showed slight die caused by anthracnose (black spots) and Mycoplasma (small blade).